Public beliefs and corruption in a repeated psychological game - Loukas Balafoutas (University of Innsbruck, Department of Public Finance, 2009)
This paper investigates the role of guilt aversion for corruption in public administration. Corruption is modeled as the outcome of a game played between a bureaucrat, a lobby, and the public. There is a moral cost of corruption for the bureaucrat, who is averse to letting the public down. We study how the behavior of the lobby and the bureaucrat depend on perceived public beliefs, when these are constant and when they are allowed to vary over time. With time-varying beliefs, corruption is more likely when the horizon of the game is relatively long and when public beliefs are initially low and are updated fast.
Keywords: C73; D73; 330; psychological games; corruption; bureaucracy; guilt; third party; Korruption; Wiederholte Spiele